Investigation on the Synergistic Complexation of Ni(II) with 1,10-Phenanthroline and Dithizone at Hexane-Water Interface Using Centrifugal Liquid Membrane-SpectrophotometryInvestigation on the Synergistic Complexation of Ni(II) with 1,10-Phenanthroline and Dithizone at Hexane-Water Interface Using Centrifugal Liquid Membrane-Spectrophotometr - Yulizar, Yoki; Wahyuningsih, Nerny; Asri, Novena Damar; Watarai, Hitoshi (UI Scholars Hub, 2012)
Complex formation of Ni(II) and 1,10-phenanthroline (C12H8N2/Phen) with the addition of dithizone (C13H12N4S/HDz) at the hexane-water interface has been studied by direct measurement spectrophotometry using the centrifugal liquid membrane (CLM) method. Ni(II) ion with Phen formed a cationic complex of Ni(C12H8N2)2 2+ or NiPhen2 2+. That complex dissolved in the aqueous phase and had two UV absorption spectrum maxima wavelengths, λmax 270 and 292 nm. Observation of complex formation was performed variations of pH and ligand concentration. The pH caused protonation that affected the amount of the formed complex. With the variations of ligand concentrations, the greater was the concentration of ligands the greater was the formed complex. Based on the Batch method, the HDz ligand addition into the NiPhen2 2+ cationic complex produced ion association complex of Ni(C13H11N4S)2(C12H8N2) or NiDz2Phen at λmax 403 nm, and was extracted in the organic phase. Measurement results using CLM method showed that NiDz2Phen complex was formed at hexane-water interface with λmax 523 nm. Comparison of Phen with HDz ligand concentrations affected the initial formation rate of NiDz2Phen complex. The greater concentration of Phen ligand increased the initial rate of formation for synergistic complex. The obtained data using CLM method indicated that the synergistic complex formation rate constant of NiDz2Phen at the interface, k was 0.30/s.